The Influences of Finance Knowledge, Financial Attitudes, and Personality on Financial Management Behaviors on Building Materials MSME - Chintya Nuranida Putri; Muhammad Azhari (Almana : Jurnal Manajemen dan Bisnis, 2021)
This research is motivated by the behavior of financial management, which is considered as one of the essential concepts in economic science, such as the allocation of acquisition and utilization of financial resources. Therefore, who conducted this research to determine financial knowledge, financial attitudes, and personality on financial management behavior in the MSME building materials players in the City of Tasikmalaya. This research design is included in the associative causality research. The subjects used were 75 building materials MSME players. The data collection technique used is primary. Data is obtained directly from the respondent. And the instrument used was a questionnaire. The data analysis technique used is Multiple Linear Regression, which is processed using software SPSS. The results showed that financial knowledge, financial attitudes, and personality partially and simultaneously had a significant effect on financial management behavior.